LIFE CYCLE COST ESTIMATION PROCEDURE FOR A WEAPON SYSTEM IN SPAIN (Journal of the Spanish Institute for Strategic Studies, 2018)
Instruction 67/2011 SEDEF/MINISDEF/ESPAÑA regulates theprocurement process of material resources accounting for their life cycle.In order to undertake an initial evaluation of the programmes that meetthe conditions of the solution required, life cycle cost estimation is used asdecision-making tool. The purpose of this paper is to present the procedurein place for estimating the life cycle costs (LCC) of programmes in Spain bycomparing it to those of the major organisations to which we belong (NATO/OCCAR), and verifying the use of historical and technical information,parameters and breakdown structures from September 2011 onwards in theLCC estimates performed.